Theoretical Analysis of Educational Cost Supervision in the Perspective of Islamic Education Management: A Systematic Literature Review - Rustandi, Feri Rustandi; Dul Wahid; Acep Ruskandar; Badrudin; Qiqi Yuliati Zakiah (Journal of Mandalika Literature, 2025)
This study aims to theoretically examine the concepts, principles, and approaches to educational cost supervision within the framework of Islamic education management, using the Systematic Literature Review (SLR) method. The focus of the review addresses two main research questions: (1) How are the concepts, principles, and approaches to educational cost supervision described in the literature on Islamic education management? and (2) How are Islamic values such as amanah (trust), justice, shura (consultation), and accountability integrated into cost supervision strategies according to previous studies? The review of 15 scholarly articles reveals that supervision of educational expenses involves not only technical and administrative dimensions but also must be grounded in Islamic ethical and spiritual values. Although the application of these principles has begun in several Islamic educational institutions, it has not yet been fully systematic or participatory. This study highlights the importance of developing a cost supervision model that integrates Islamic ethical values, stakeholder involvement, and value-based audit systems. It recommends that future research adopt an empirical approach to test the practical effectiveness of implementing Islamic values in financial supervision within educational institutions.